The effect of obesogenic and inflammatory factors in regulating adipocytes lipid chaperone proteins - Mohd Radzuan, Hazulin (2020)
It has been increasingly clear that adipose tissue (AT) actively secretes lipid chaperone proteins (LCPs) into circulatory system without preceding tissue injury or cell death event. Among them are fatty acid binding protein 4 (FABP4), which is known to be increased in inflammatory condition despite of absence of any secretion directed signals; and lipocalin2 (LCN2), which function is still debatable since there are evidences supporting its role in both pro and anti-inflammatory states.